Stent luxation: Possible complication of subadventitial stenting in coronary chronic total occlusion revascularization. Issue 5 (5th May 2016) - Dautov, Rustem; Nguyen, Can M; Rinfret, Stéphane
Abstract : The entry to the subadventitial space is not a mode of failure, but the road to success in many chronic total occlusion (CTO) percutaneous coronary intervention (PCI) cases. Long‐term clinical outcomes of subadventitial stenting are favorable and similar to intraluminal stenting. However, the subadventitial space histology and physiology remains different to the coronary true intraluminal space. We report a complication specific to stenting of the subadventitial space, where overlapping stents dislocated from one another, which resulted in late non‐occlusive stent thrombosis. We describe, for the first time in the literature, this complication, possible reasons behind, and the ways to avoid this potentially major mischief. © 2016 Wiley Periodicals, Inc.